Volume 1: Fora, Parts A, B, C, and D 2003
DOI: 10.1115/fedsm2003-45647
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble Drag Reduction in Rough Walled Turbulent Boundary Layers

Abstract: Experiments were conducted in the 12-inch diameter tunnel at ARL/PSU using the tunnel wall boundary layer facility to determine the influence of surface roughness on microbubble drag reduction. To accomplish this, carbon dioxide was injected through a slot at rates of 0.001 m3/s to 0.011 m3/s, and the resulting skin friction drag measured on a 317.5 mm long by 152.4 mm span balance. In addition to the hydrodynamically smooth balance plate, additional plates were covered with roughly 75, 150 and 300 micron grit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Good agreement was achieved between the simulations with the single phase model and experimental data of Deutsch et al (2003). This good agreement was observed for both free stream velocity as well as surface roughness effect studies.…”
Section: Executive Summarysupporting
confidence: 66%
See 4 more Smart Citations
“…Good agreement was achieved between the simulations with the single phase model and experimental data of Deutsch et al (2003). This good agreement was observed for both free stream velocity as well as surface roughness effect studies.…”
Section: Executive Summarysupporting
confidence: 66%
“…The results of our model are very close to those of Kunz et al model, however, both models over predict experimentally observed drag reduction by as much as 50% in some cases. To facilitate comparison of simulations with experimental study of Deutsch et al (2003) on the influence of surface roughness on microbubble drag reduction a slightly modified computational domain was used. This domain is shown schematically in Figure 6.…”
Section: Single Phase Modelmentioning
confidence: 99%
See 3 more Smart Citations